2017
DOI: 10.1080/13102818.2017.1308231
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of expression and purification of recombinant S1 domain of the porcine epidemic diarrhea virus spike (PEDV- S1) protein inEscherichia coli

Abstract: The PEDV-S1 protein, one of the members of a large family of PEDV, is significantly upregulated and has been targeted as a biomarker of cellular stress in several studies. Herein, conditions were optimized to increase the yield of recombinant PEDV-S1 protein in its native state, primarily focusing on the optimization of upstream processing parameters that lead to an increase in the specific as well as volumetric yield of the protein. The results showed that the production of PEDV-S1 was increased proportionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that after adding the IPTG into the medium, the target protein begins to be synthesized and post-induction incubation time is necessary for recombinant protein production. The duration of post-induction incubation affects the overall folding, accumulation, and productivity of recombinant proteins in E. coli (Wong et al, 1998), and is affected by several factors such as strength of promotor, inducer concentration, solubility, and intrinsic properties of recombinant proteins (Noi and Chung, 2017). Our results suggest that the optimal post-induction incubation time for the highest expression of recombinant P97R1R2 protein in E. coli BL21(DE3) cells is 6 h.…”
Section: Optimization Of Incubation Timementioning
confidence: 82%
“…Previous studies have reported that after adding the IPTG into the medium, the target protein begins to be synthesized and post-induction incubation time is necessary for recombinant protein production. The duration of post-induction incubation affects the overall folding, accumulation, and productivity of recombinant proteins in E. coli (Wong et al, 1998), and is affected by several factors such as strength of promotor, inducer concentration, solubility, and intrinsic properties of recombinant proteins (Noi and Chung, 2017). Our results suggest that the optimal post-induction incubation time for the highest expression of recombinant P97R1R2 protein in E. coli BL21(DE3) cells is 6 h.…”
Section: Optimization Of Incubation Timementioning
confidence: 82%
“…10,40 The addition of the inducer during the lag phase makes bacterial growth difficult; its addition during the stabilization phase inhibits the expression of the target gene. 41 Generally, the optimal OD 600 interval for gene induced expression should be in the range of 0.5-0.8. In this study, the OD 600 was selected as 0.6, and the culture time was 2 h. The optimal induce conditions were 1.0 mM IPTG, 5 h, and 30 C. Aer protein extraction, isolation, and purication, the expression of the nosZ gene was examined by SDS-PAGE gel electrophoresis, and the results were shown in Fig.…”
Section: N 2 or Expression In Recombinant E Colimentioning
confidence: 99%
“…These include immunogens based on the S1 moiety [11], the S2 moiety [12], and a smaller portion known as the core neutralizing epitope or COE (amino acids 499-638) that has been identified as containing neutralizing epitopes [13]. However, the prototype vaccines require the purification of the S protein, which has been difficult to produce at high levels in several recombinant systems [11,14,15].…”
Section: Introductionmentioning
confidence: 99%